'Martinique is ours, not theirs!': framing conflicting identities during the 2009 protests. Issue 2 (3rd April 2019) - Théodose, Céline
ABSTRACT: This article undertakes a close analysis of the general strike that occurred in the French department of Martinique in 2009, which brought most economic activities on the island to a standstill for 38 days. The movement was a privileged site for observing how the integration of Martinique into the French nation state was thwarted by the politics of departmentalisation. The protests created a liminal space that allowed protesters to contest the resilience of colonial discourses and to voice alternative identity narratives. This open space was an integrative space, and the ultimate rhetorical bond that unified the protesters in the performance of communitas . The discussion of this historical event presents an alternative reading to theoretical debates about the multifaceted relationships between nationalism and collective memories in postcolonial settings in general, and on the impacts of social movements in the reconstruction of national identities in particular.